Microbiological spectrum and antibiotic susceptibility analysis of secretion from 308 cases of chronic dacryocystitis in north China - Yue-Qing He; Xiao-Bo Tian; Yang Zhang; Hua Sun (International Journal of Ophthalmology)
AIM: To determine the microbiological agents and antibiotic susceptibility of chronic dacryocystitis in recent years to guide effective treatment strategies. METHODS: A total of 308 adult patients with chronic dacryocystitis were enrolled from January 2020 to September 2022 in Beijing Tongren Hospital. The 229 pus specimens were taken from the conjunctival sac, while 79 specimens were taken from the opened lacrimal sac during transnasal dacryocystorhinostomy (DCR) surgery. All the samples were sent for microbiological smear and culture and drug susceptibility tests. RESULTS: The 202 specimens showed microbial growth, with a positive rate of 65.6%. The 313 strains of bacteria were isolated, including 272 aerobic or facultative anaerobes, accounting for 86.9%, and 41 anaerobic bacteria, accounting for 13.1%. The most common strains were Staphylococcus epidermidis, Corynebacterium macginleyi, and Staphylococcus aureus. Six strains of fungi were isolated. The 14 strains (18.9%) of Staphylococcus were found to be multidrug resistant. It showed a wide variety of gram-negative bacteria, up to 23 species. Specimens obtained during DCR surgery had a positive rate of 70.9%, which was higher than those obtained from the conjunctival sac (63.8%), with a statistically significant difference. More microbiological species were found in intraoperative specimens, and consisted largely of pathogenic bacteria or conditional pathogens. All the 6 strains of fungi were obtained from intraoperative specimens. All bacteria were sensitive to vancomycin, while a large number of bacteria were resistant to erythromycin. The commonly used ocular antibiotics levofloxacin, moxifloxacin and tobramycin were generally sensitive to most of the bacteria. CONCLUSION: Gram-positive cocci, gram-positive bacilli, and gram-negative bacilli are the predominant pathogens for chronic dacryocystitis. Specimens taken during DCR surgery can obtain more accurate microbiological results.